2012
DOI: 10.4048/jbc.2012.15.1.7
|View full text |Cite
|
Sign up to set email alerts
|

Surgical Techniques for Personalized Oncoplastic Surgery in Breast Cancer Patients with Small- to Moderate-Sized Breasts (Part 2): Volume Replacement

Abstract: Oncoplastic breast surgery has become a popular choice of treatment for breast reconstruction after mastectomy. There are two different techniques in oncoplastic surgery depending on the volume of the excised breast tissue. One is the volume displacement procedure, which combines resection with a variety of different breast-reshaping and breast-reduction techniques; the other is the volume replacement procedure in which the volume of excised breast tissue is replaced with autologous tissue. In this study, curr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
47
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 46 publications
(47 citation statements)
references
References 23 publications
(24 reference statements)
0
47
0
Order By: Relevance
“…The esthetic results of surgery can be improved by removing less breast tissue after NACT, and shrinking the tumor and preserving the breast skin simplifies breast reconstruction [7,8]. However, esthetic problems resulting from BCS need to be improved [9]. Removing 20 % of the breast volume decreases breast aesthetics [7,9].…”
Section: Introductionmentioning
confidence: 98%
See 1 more Smart Citation
“…The esthetic results of surgery can be improved by removing less breast tissue after NACT, and shrinking the tumor and preserving the breast skin simplifies breast reconstruction [7,8]. However, esthetic problems resulting from BCS need to be improved [9]. Removing 20 % of the breast volume decreases breast aesthetics [7,9].…”
Section: Introductionmentioning
confidence: 98%
“…However, esthetic problems resulting from BCS need to be improved [9]. Removing 20 % of the breast volume decreases breast aesthetics [7,9]. A wide section of the breast may need to be removed in LABC, and the glandular defect that may form can jeopardize the aesthetics.…”
Section: Introductionmentioning
confidence: 98%
“…An average tumor size of 32 mm in a series of 101 therapeutic mammoplasties was reported by the former study, while the latter reported an average size of 23.9 mm in 37 OPS patients. Similarly, previous studies have reported specimen weights for therapeutic mammoplasty ranging from 222-236 g [1,17]. In relation to the operative times, those patients who underwent a wide local excision (WLE group) spent a shorter time in theatre compared to those who underwent oncoplastic surgery (OPS).…”
Section: Discussionmentioning
confidence: 99%
“…The skin defect is also replaced. A similar technique, myosubcutaneous LD flap (mini LD flap) fills in the defect with LD flap, the skin is not transferred in this technique (5,26). Endoscopic LD mini flap applications are being developed with access sites from the breast and axilla (27).…”
Section: A-breast Volume Displacement;mentioning
confidence: 99%
“…Despite advances in surgical techniques, positive margin rates in breast cancer following BCS is reported as 20-30% (4,5). The rate of aesthetic problems in conservative surgery that are not amenable for surgical correction have been reported as 30% (6).…”
Section: Introductionmentioning
confidence: 99%